Analyzing Agricultural Trade-Off and Composing Strategies to Advance Sustainable Development - Prajanti, Sucihatiningsih Dian Wisika; Pratama, Bayu Rizky; Amelia, Dhea Rizky; Adzim, Fauzul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
Agriculture takes an important role for economy by more than 14% of economic contribution. Nevertheless, it has indirective effects, where it has commonly a negative impact, but somehow in the long term, offers a better environmental service. This study, therefore, aimed to evaluate both impact by estimating the Indonesia food barn to estimate how far the impact to environment through the Environmental Kuznets Curve (EKC). In order to improve the environmental quality in the long term, the sustainable practices through ecolabelling product have to be conducted. Thus, the evaluation of consumers’ WTP for ecolabelling product has been observed through 300 respondents depicting their preferences. Following by AHP analysis to construct the priority of strategies to develop the sustainable agriculture. Based on the results, EKC model showed it initially leads to environmental damage, but at a certain level, people begin to increase environmental awareness by a decrease of methane (CH4) about 0.12%. It is proved by their WTP where 82.6% respondents were willing to pay for ecolabelling product. Finally, to support sustainable agriculture, reforming the market access is a top priority (0.312 points) which aimed to progressively encourage the farmers’ supply. Otherwise, the pricing strategy becomes the consumers’ main perspective to buy (0.264 points).